Editorial - Vedula, Krishna (Journal of Engineering Education Transformations, 2017)
We are delighted to announce that JEET is now in the UGCApproved List of Journals (Journal number 47931, ISSN # 23492473under http://www.ugc.ac.in/journallist/). Please spread the word, so that your colleges will be motivated to subscribe and we can increase the readership of the Journal. Please encourage your institutional leaders and colleagues to make JEET as an important part of their efforts to improve quality of engineering education. This will not only increase readership but will also help us move towards a better financial situation.